The Beloved Self: Morality and the Challenge from Egoism - Hills, A (Oxford University Press, 2010)
The Beloved Self is about the 'holy grail' of moral philosophy: an argument against Egoism, that we all have reasons to be moral. The first part of the book introduces three versions of Egoism, each paralleling a different moral theory, and sheds new light on the concept of self-interest in virtue ethics and especially in Kant's moral theory. Part Two looks at attempts to prove that Egoism is false, and shows that even modest arguments against Egoist appear to fail. Part Three discusses the relationship between knowledge and action and defends a new conception of moral epistemology, centred on the importance of moral understanding, which has wide-ranging implications regarding not only moral testimony and moral disagreement but also the nature of virtue and morally worthy action. This final part of the book culminates in a vindication of morality, an argument that it is not epistemically rational to believe the most plausible versions of Egoism.